Evaluation the salivary glucose as a potential diagnostic tool in diabetic patients (type 2) - Brbahan, Mkdad Adeb; Zriki, Samira Sadik; Radwan, Fisal Najib (Journal of medical and pharmaceutical sciences, 2021)
Diabetes mellitus (type 2) is a chronic metabolic disease that accounts for 90-95% of all diabetic patients. It leads to many changes in the small blood vessels, peripheral nerves and vital organs and affects the immunity and the oral cavity with its structure and the composition of its parts, such as saliva, which contains glucose. Early detection of diabetes helps delay its complications and requires a procedure (venous blood sample or finger prick) which is often painful, which prevents patients from adhering to frequent screening or delayed detection of diabetes. Therefore, researchers tended to look for simpler procedures.Aims: To make a comparison between salivary glucose levels in patients with diabetes (type 2) and in healthy individuals to reveal the possibility of using these levels as a measure to monitor diabetes.Materials and Methods: The sample included 100 diabetics and reviewers for the Diabetes Center in Lattakia, their ages ranged from 40 to 70 years, in addition to the control group consisting of 100 others correlated with age and gender. The study members were asked to refrain from eating anything an hour before, saliva was collected, and samples were collected between 8-9 a.m. by spitting into a graduated container every minute until we got 5 ml of saliva, and centrifugation was performed and samples were analyzed using a spectrophotometer. After that, blood samples were taken and blood glucose analysis was performed.Results: The mean salivary glucose concentration was significantly greater in type 2 diabetes (20.46 mg/dl) compared to healthy individuals (7.27 mg/dl), and the correlation between them was very strong (0.8), and p-value = 0.000 (>0.01).Conclusions & Recommendations: Based on the above, we conclude that the value of saliva glucose in a patient with diabetes (type 2) is more than two and a half times greater than that of a healthy person. And we recommend the use of salivary glucose as a measure to monitor blood glucose levels in patients with diabetes (type 2).
Keywords: diabetes mellitus (type 2); salivary glucose; blood sugar; saliva